Understanding Consumer Sentiments: Exploring the Role of Artificial Intelligence in Marketing - Shereen Noranee; Abdul Kadir bin Othman (Universitas 17 Agustus 1945 Surabaya, 2023)
This research article presents a comprehensive review of the industrial opportunities of AI in marketing. The study begins with an introduction highlighting the significance of AI in marketing and its transformative potential. The literature review focuses on three key aspects: understanding consumer sentiments, market insights, and the use of AI in marketing. The review highlights the role of AI in understanding consumer sentiments through sentiment analysis, enabling marketers to gain valuable market insights. It explores the industrial opportunities of AI, including personalized marketing, predictive analytics, and customer segmentation. Additionally, the review discusses the use of AI in enhancing customer satisfaction, improving electronic word-of-mouth insights, and measuring market performance. The research methodology involved a systematic review of academic articles, industry reports, and conference papers. The findings reveal that AI-driven market sentiment analysis uncovers significant patterns, trends, and correlations in consumer sentiment data. This enables marketers to make data-driven decisions and develop effective marketing strategies. The implications of these findings for marketing strategies and decision-making processes are discussed. In conclusion, this research emphasizes the industrial opportunities of AI in marketing and provides insights for practitioners and researchers. Leveraging AI technologies can enhance market insights, improve customer satisfaction, and optimize marketing performance. The study contributes to the understanding of AI's application in marketing and serves as a foundation for future research. Marketers are encouraged to embrace AI to gain a competitive edge in the evolving marketing landscape.